The association between Chinese eye exercises and myopia in children and adolescents: A systematic review and meta-analysis - Tang, Jie; Pei, Yifei; Wang, Jingjing; Yan, Na; Luo, Yunjiao; Zhou, Wen; Wang, Xiaojuan; Wang, Wei (Frontiers in Public Health, 2023)
Objective This study aims to summarize the relevant evidence on the association between eye exercises and myopia in children and adolescents in China. Methods The meta-analysis pooled the results of 12 studies, with a total of 134,201 participants. Another five studies (no OR for myopia as an outcome and meeting inclusion criteria) were reported in the systematic review. We searched PubMed, Web of Science, CNKI, Wan Fang, and reference lists of retrieved studies. Association estimates were pooled using random-effects meta-analyses. Odds ratios (ORs) and 95% confidence intervals (CIs) for eye exercises and myopia were pooled from a meta-analysis. Results After standardizing the reference values, a pooled OR of the univariate analysis showed a 24% reduction in myopia in children and adolescents who performed eye exercises (OR = 0.76; 95% CI: 0.62–0.89). After adjusting the covariate, a pooled OR of multiple logistic analysis for myopia (OR = 0.87; 95% CI: 0.72–1.02) showed that there is no significance between eye exercises and myopia. However, in subgroup studies of the multivariate analysis, the large sample (OR = 0.84; 95% CI: 0.74–0.94) and Chinese database (OR = 0.80; 95% CI: 0.67–0.93) subgroup showed modest protective effects. In addition, five studies in the systematic review also evaluated the risk of myopia events, and Chinese eye exercises had a modest protective effect on myopic control, but the incorrect performance of and attitude toward eye exercises posed negative effects on their eyesight health. Conclusion Chinese eye exercises have a modest protective effect on myopic control, but considering that the incorrect performance of and attitude toward eye exercises have a significant influence on the effect of eye exercises, the effect of eye exercises may not be enough to prevent the progress of myopia in the long term, and more standardized eye exercises need to be conducted.